Jupiter's Gravity Field Halfway Through the Juno Mission. Issue 4 (11th February 2020) - Durante, D.; Parisi, M.; Serra, D.; Zannoni, M.; Notaro, V.; Racioppa, P.; Buccino, D. R.; Lari, G.; Gomez Casajus, L.; Iess, L.; Folkner, W. M.; Tommei, G.; et al.
Abstract: The Juno spacecraft reached the mid‐point of its nominal mission in December 2018, after completing 17 perijove passes. Ten of these were dedicated to the determination of the gravity field of the planet, with the aim of constraining its interior structure. We provide an update on Jupiter's gravity field, its tidal response and spin axis motion over time. The analysis of the Doppler data collected during the perijove passes hints to a non‐static and/or non‐axially symmetric field, possibly related to several different physical mechanisms, such as normal modes or localized atmospheric or deeply‐rooted dynamics. Plain Language Summary: Jupiter's gravity field has been updated with the use of Juno's data collected up to the mid‐point of its mission. The field is largely symmetric about the rotation axis, and shows conspicuous north‐south asymmetry. Possible non‐static and/or non‐axially symmetric field is compatible with the data. Key Points: Juno updates Jupiter's gravity field halfway through its mission, revealing a largely axially symmetric, north‐south asymmetric field Hints to a non‐static and/or non‐axially symmetric field, possibly related to several different physical mechanisms, appear in the data The tidal response is evaluated and compared to interior model predictions